Investigasi Bidang Gelincir Tanah Longsor Menggunakan Metode Geolistrik Tahanan Jenis di Desa Kebarongan Kec. Kemranjen Kab. Banyumas - Sugito, Sugito; Irayani, Zaroh; Permana Jati, Indra (BERKALA FISIKA, 2010)
Investigation of landslide slip surface using geoelectrical resistivity method has been conducted at Kebarongan Village, Kemranjen District, Banyumas Regency. Data acquisition by means Schlumberger and Wenner configuration.  Data processing and interpretation were using Progress version 3.0 and Res2Dinv version 3.54 softwares.  The output of Progress software were depth, number of layers, and values of rock resistivity.  Mean while the output of Res2Dinv were resistivity section, RMS, and depth of rock layers.  The interpretation result showed that at Kebarongan village lithology consist of four layers i.e. top soil, sandy clay, wet clay and sandy clay.  Slip surface is wet clay with depth of 10.31 until 14.21 m.  The slip surface orientation is same of slope area that is to south and the type of landslide is translational.      Keywords: geoelectrical resistivity, landslide, slip surface, Kebarongan